End-of-Life Decision-Making in Colorectal Surgery - Moon, Jeongyoon; Somomvilla, Josh (Clinics in Colon and Rectal Surgery, 2025)
Shared decision-making (SDM) has emerged as a cornerstone of patient-centered care in the surgical setting. Surgeons can provide their opinion based on evidence and expertise, while patients provide their unique values and preferences—culminating in a unified plan. This is especially important at the end-of-life. This chapter will explore the unique role and benefit that SDM has in end-of-life situations and provide a context in which to navigate these difficult times.
Keywords: shared decision-making; end-of-life; palliative care